Dengue virus persists and replicates during storage of platelet and red blood cell units. Issue 5 (18th January 2016) - Sutherland, Michael R.; Simon, Ayo Y.; Serrano, Katherine; Schubert, Peter; Acker, Jason P.; Pryzdial, Edward L.G.
Abstract : BACKGROUND: Dengue virus (DENV) is a transfusion‐transmissible arbovirus that threatens blood donor systems with approximately 200 million high‐titer asymptomatic infections occurring annually. Here we investigated the viability of DENV during storage of donor‐derived platelet (PLT) and red blood cell (RBC) units. While purified PLTs have been shown to generate viable DENV, RBCs are replication incompetent. Combined with different storage criteria, distinct virus persistence profiles were anticipated in PLT and RBC units. STUDY DESIGN AND METHODS: Mimicking the virus titer of asymptomatic donors, purified DENV was spiked (10 5 ‐10 6 infectious units/mL) into PLT or RBC units produced and stored according to blood bank operating procedures. DENV was measured by infectious plaque‐forming assays and by quantitative reverse transcription–polymerase chain reaction. RESULTS: In both PLT (7 days, 20‐24°C) and RBC (42 days, 1‐6°C) units, infectious DENV persisted throughout storage despite logarithmic decay. In buffer alone, DENV infectivity was insignificant by Day 1 at 20 to 24°C or 14 days at 1 to 6°C. Infectious virus production was identified in stored PLT units using a translation inhibitor and supported by virus genome replication. Surprisingly, DENV was also produced in RBC units, implying the involvement of cells other than RBCs. CONCLUSION: Both virus propagation and effects independent of cell function mitigate the intrinsic lability of DENV. Nevertheless, the overall rapid storage decay suggests that aged PLT and RBC units may be safer. These data raise awareness to the possible persistence of other conceivably more robust RNA viruses during the storage of cellular blood products.